2009
DOI: 10.1186/1476-069x-8-15
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood lead concentrations with mortality in older women: a prospective cohort study

Abstract: BackgroundBlood lead concentrations have been associated with increased risk of cardiovascular, cancer, and all-cause mortality in adults in general population and occupational cohorts. We aimed to determine the association between blood lead, all cause and cause specific mortality in elderly, community residing women.MethodsProspective cohort study of 533 women aged 65–87 years enrolled in the Study of Osteoporotic Fractures at 2 US research centers (Baltimore, MD; Monongahela Valley, PA) from 1986–1988. Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 68 publications
2
37
0
1
Order By: Relevance
“…Lead is known to induce a wide range of biochemical and physiological dysfunctions to humans and laboratory animals. Recent epidemiological studies have revealed that increased level of lead in the blood has an association with several disease outcomes such as hypertension, peripheral artery diseases, kidney diseases, neurodegenerative diseases and cognitive impairments [10][11][12]. Lead exposure is also implicated in a broad clinical spectrum of disease, including hematological, renal, cardiovascular, neurological, developmental and behavioral disorders [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead is known to induce a wide range of biochemical and physiological dysfunctions to humans and laboratory animals. Recent epidemiological studies have revealed that increased level of lead in the blood has an association with several disease outcomes such as hypertension, peripheral artery diseases, kidney diseases, neurodegenerative diseases and cognitive impairments [10][11][12]. Lead exposure is also implicated in a broad clinical spectrum of disease, including hematological, renal, cardiovascular, neurological, developmental and behavioral disorders [13].…”
Section: Introductionmentioning
confidence: 99%
“…Literature reports have also revealed that lead is a toxic heavy metal associated with a number of health problems to individuals exposed to it [6,[10][11][12][13]. However, there was no previous study carried out to understand the levels to which the roadside soils of the eastern towns of Ethiopia; namely, Bishoftu, Modjo, and Adama towns were polluted by lead accumulation originated from the heavy vehicular densities.…”
Section: Introductionmentioning
confidence: 99%
“…However, this observation was still higher than the recently reported blood Pb for the general populations in other countries (18~33 ng/mL) [24,64,66,67]. A similar blood Pb level (53±23 ng/mL) was found in older women in the USA [70]. Although in general the blood Pb level has declined in recent years, current levels may still result in adverse health effects that should not be ignored [70][71][72][73][74].…”
Section: Leadmentioning
confidence: 42%
“…Vários autores referem que o uso de canalizações para abastecimento de água feitas de chumbo provoca graves de problema de saúde, o que se fica a dever à formação de uma película de produtos de corrosão na superfície interna da tubagem, a qual acaba por ser lixiviada e contaminar a própria água (ZIETZ et al, 2009 Tem-se presente que um teor de chumbo no sangue acima de 10 μg/dl se considera como valor de envenenamento (LABAT et al, 2006;TARARBIT CARRÉ;GARNIER, 2009), estando associado à mortalidade cardiovascular e ao aparecimento de cancro. Mais recentemente, Khalil et al (2009) referem um risco acrescido de morte em pessoas idosas para concentrações de chumbo no sangue acima de 8 μg/dl. Outros (MENKE et al, 2006) observaram risco de enfarte de miocárdio e acidente vascular cardíaco (AVC) para níveis acima de 2 μg/dl.…”
Section: Materiais Que Libertam Fumos Tóxicos Em Caso De Incêndiounclassified